Four seasons maize yield experiment on tillage and fertilizer options in Tanzania - Mtakwa, Peter W.; Hijbeek, Renske; Loon, Marloes P. van; Urio, Ndelilio A.; Mtakwa, Alpha P.; Brentrup, Frank; Tibezukwa, George; ten Berge, Hein F.M.; Ittersum, Martin K. van (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This poster presents key results from the Bringing Climate-Smart Agriculture practices to scale: assessing their contributions to narrow nutrient and yield gaps project under the CCADS Low-Emissions Development Flagship.